Public Budgeting in Theory and Practice: A Comprehensive Overview - Syeda Sadia Ambreen Jilani, (BNBWU Journal of Multidisciplinary Research, 2025)
This study provides a comprehensive exploration of public budgeting from both theoretical and practical perspectives. Tracing the historical evolution of the budget concept from its origins in 18th-century Britain, it defines the budget as a fiscal blueprint encompassing a government's projected revenues and expenditures. The paper elaborates on the three essential financial functions of government economic stability, development, welfare and analyzes various budget structures, including balanced, surplus, and deficit budgets. A central focus is the classification and evaluation of nine distinct budgeting methodologies: static, flexible, functional, master, zero-based, participative, imposed, rolling, and annual budgets. Each is assessed for its strategic application, benefits, and limitations in real-world economic governance. The study emphasizes budgeting as a vital instrument for achieving fiscal responsibility, transparency and efficient resource allocation. Ultimately, it underscores that a deep understanding of budgeting practices is crucial for effective public administration, economic planning, and national development.